Case Study on Human Walking during Wearing a Powered Prosthetic Device: Effectiveness of the System "Human-Robot". (9th January 2014) - Grosu, Svetlana; Cherelle, Pierre; Verheul, Chris; Vanderborght, Bram; Lefeber, Dirk
Abstract : It is known that force exchanges between a robotic assistive device and the end-user have a direct impact on the quality and performance of a particular movement task. This knowledge finds a special reflective importance in prosthetic industry due to the close human-robot collaboration. Although lower-extremity prostheses are currently better able to provide assistance as their upper-extremity counterparts, specific locomotion problems still remain. In a framework of this contribution the authors introduce the multibody dynamic modelling approach of the transtibial prosthesis wearing on a human body model. The obtained results are based on multibody dynamic simulations against the real experimental data using AMP-Foot 2.0, an energy efficient powered transtibial prosthesis for actively assisted walking of amputees.